A Comparative Clinical Evaluation of the efficacy of two Desensitizing dentifrices in Relieving Dentine Hypersensitivity (Nepal Medical College Journal, 2020)
Dentinal hypersensitivity has been defined as a short, sharp pain arising from exposed dentine in response to stimuli thermal, evaporative, tactile, chemical or osmotic and which cannot be ascribed to any other form of dental defect or pathology. This is a common clinical condition which may cause patients more distress due to exposure of dentin. There are various management options for this clinical condition which can be either home applied or in office techniques. Various dentifrices are commercially available in the market. The chemical compositions of the dentifrices are different. We conducted this study to compare the effectiveness of a potassium nitrate containing dentifrice and a Novamin based dentifrice in relieving dentinal hypersensitivity. The patients were divided into two experimental groups; group 1-potassium nitrate containing dentifrice and group 2-Novamin containing dentifrice. The sensitivity score was analyzed by using a verbal rating scale at baseline, at three weeks and at six weeks after using the dentifrices. Statistical analysis was done using SPSS version 17. Chi-square test showed that there was no significant difference between the effectiveness and efficacy of the two dentifrices. The results were highly significant (p